2003
DOI: 10.1007/s00535-002-1081-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel diamino-pyridine derivative (IS-741) attenuates rat ileitis induced by trinitrobenzene sulfonic acid

Abstract: These results indicate that the oral administration of IS-741 inhibits neutrophil infiltration into inflamed lesions, and is effective for attenuating rat TNBS ileitis. This new anti-inflammatory agent may be beneficial for the treatment of inflammatory bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Yotsuya et al 30 suggested that IS-741 inhibited the cluster formation of LFA-1 with activation of LFA-1. In previous studies, IS-741 has been proven to have therapeutic effects in some animal models of acute pancreatitis, 20,22 ileitis, 23 and colitis, 19,24 and it is supposed that the mechanism by which IS-741 prevents the development of inflammation might be due to its inhibitory effects on the adhesion of neutrophils to endothelial cells and subsequent neutrophil infiltration into the tissue. As above, the antiinflammatory effects of IS-741 on acute inflammation with neutrophil infiltration were reported; however, the effect of IS-741 on chronic inflammation and fibrosis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yotsuya et al 30 suggested that IS-741 inhibited the cluster formation of LFA-1 with activation of LFA-1. In previous studies, IS-741 has been proven to have therapeutic effects in some animal models of acute pancreatitis, 20,22 ileitis, 23 and colitis, 19,24 and it is supposed that the mechanism by which IS-741 prevents the development of inflammation might be due to its inhibitory effects on the adhesion of neutrophils to endothelial cells and subsequent neutrophil infiltration into the tissue. As above, the antiinflammatory effects of IS-741 on acute inflammation with neutrophil infiltration were reported; however, the effect of IS-741 on chronic inflammation and fibrosis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Recently, IS-741 was also shown to inhibit the expression of Mac-1 (CD11b/CD18) or LFA-1 (CD11a/CD18), a cell adhesion molecule on the surface of circulating neutrophils, 19,20 and block the adhesion between inflammatory cells and microvascular endothelial cells in vivo and in vitro. In previous studies, it has been demonstrated that treatment with IS-741 significantly attenuated inflammation in various inflammatory experimental models such as acute pancreatitis, 20Y22 ileitis, 23 and colitis. 19,24 The mechanism by which IS-741 prevents the development of acute pancreatitis and colitis might be due to its inhibitory effects on the adhesion of neutrophils to endothelial cells and subsequent neutrophil infiltration into the pancreatic tissue or intestinal mucosa of colon.…”
mentioning
confidence: 99%